International comparisons of the associations between objective measures of the built environment and transport-related walking and cycling: IPEN adult study. Issue 4 (December 2016) - Christiansen, Lars B.; Cerin, Ester; Badland, Hannah; Kerr, Jacqueline; Davey, Rachel; Troelsen, Jens; van Dyck, Delfien; Mitáš, Josef; Schofield, Grant; Sugiyama, Takemi; Salvo, Deborah; Sarmiento, Olga L.; et al.
Abstract: Introduction: Mounting evidence documents the importance of urban form for active travel, but international studies could strengthen the evidence. The aim of the study was to document the strength, shape, and generalizability of relations of objectively measured built environment variables with transport-related walking and cycling. Methods: This cross-sectional study maximized variation of environments and demographics by including multiple countries and by selecting adult participants living in neighborhoods based on higher and lower classifications of objectively measured walkability and socioeconomic status. Analyses were conducted on 12, 181 adults aged 18–66 years, drawn from 14 cities across 10 countries worldwide. Frequency of transport-related walking and cycling over the last seven days was assessed by questionnaire and four objectively measured built environment variables were calculated. Associations of built environment variables with transport-related walking and cycling variables were estimated using generalized additive mixed models, and were tested for curvilinearity and study site moderation. Results: We found positive associations of walking for transport with all the environmental attributes, but also found that the relationships was only linear for land use mix, but not for residential density, intersection density, and the number of parks. Our findings suggest that there may be optimum values in these attributes, beyond which higher densities or number of parks could have minor or even negative impact. Cycling for transport was associated linearly with residential density, intersection density (only for any cycling), and land use mix, but not with the number of parks. Conclusion: Across 14 diverse cities and countries, living in more densely populated areas, having a well-connected street network, more diverse land uses, and having more parks were positively associated with transport-related walking and/or cycling. Except for land-use-mix, all built environment variables had curvilinear relationships with walking, with a plateau in the relationship at higher levels of the scales. Highlights: International study with comparable methods. Associations between built environment(BE) and active transport(AT). Finding both linear and curvilinear relationships. Adding to the discussion on generalizability across countries.